A Bird Survey of Gunung Lumut Protection Forest, East Kalimantan and a Recommendation for its Designation as an Important Bird Area - Part 1 - Ben Wielstra; Sander M Pieterse (Indonesian Ornithologists’ Union, 2009)
We report on a bird survey in and near Gunung Lumut Protection Forest in East Kalimantan, and evaluate our results against the BirdLife International criteria for recognition as an Important Bird Area. Five globally threatened species (Storm 's Stork Ciconia stormi, Bomean Peacock-pheasant Polyplectron schleiermacheri, Large Green Pigeon Treron capellei, Short-toed Coucal Centropus rectunguis and Blue-headed Pitta Pitta baudii) were encountered, as well as 91 species endemic to the Sundaic Lowland Forest biome, and up to 1% of the biogeographic population of the congregatory Storm's Stork. Based on these observations, we recommend Gunung Lumut Protection Forest to be included in Birdlife International 's Important Bird Area network.